2021
DOI: 10.3390/buildings11040174
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Air Change Rate by Selected Methods in a Typical Apartment Building

Abstract: An important parameter that affects indoor climate of buildings and also ventilation heat losses and gains is the speed of air change between the outdoor environment and the interior of buildings. Indoor air quality is therefore significantly associated with ventilation. Quantification of air change rate is complicated, because it is impacted by many parameters, the most variable of which is air flow. This study focuses on the determination and comparison of air change rate values in two methods by quantificat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…TB cases occur due to inadequate ACH which potentially transmit TB bacteria to the house occupants. ACH depends on the speed and movement of air entering and leaving the house (16). Expanding ventilation such as opening windows and doors every day can reduce the number of contaminants at the house (17).…”
Section: Multivariate Analysis Resultsmentioning
confidence: 99%
“…TB cases occur due to inadequate ACH which potentially transmit TB bacteria to the house occupants. ACH depends on the speed and movement of air entering and leaving the house (16). Expanding ventilation such as opening windows and doors every day can reduce the number of contaminants at the house (17).…”
Section: Multivariate Analysis Resultsmentioning
confidence: 99%
“…In our study bedrooms, natural ventilation was the predominant ventilated type during the periods of sampling, the ventilation rate closed to the previous studies that calculated values. 51,52 However, the ventilation rates were higher in the daytime than in the nighttime during the hot season. Studies have demonstrated that AC use reduces the ventilation rate.…”
Section: Discussionmentioning
confidence: 98%
“…However, the ventilation rates were higher in the daytime than in the nighttime during the hot season. Studies have demonstrated that AC use reduces the ventilation rate 51,53 . In the hot season, hours of AC use were higher at nighttime than at daytime in the children’s bedrooms (Table S4).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations